2014
DOI: 10.1111/1471-0528.12666
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between postpartum levator ani muscle avulsion and signs and symptoms of pelvic floor dysfunction

Abstract: Objective To establish the relationship between postpartum levator ani muscle (LAM) avulsion and signs and/or symptoms of pelvic floor dysfunction (PFD).Design Observational longitudinal cohort study.Setting District General University Hospital, UK.Population or sample Primigravida at 36 weeks' gestation and 3 months postpartum.Methods Pelvic floor muscle strength (PFMS) and pelvic organ prolapse were assessed clinically using validated methods. Transperineal ultrasound was performed to identify LAM avulsion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 49 publications
1
74
1
Order By: Relevance
“…It could not yield any data on fasciae and pelvic floor muscles. MRI especially dynamic MRI is one of the most important methods that has been considered in the recent years as it is not invasive and could yield visualization of all soft tissues and pelvic compartments (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Different MRI sequences and protocols could assess these structures.…”
Section: Introductionmentioning
confidence: 99%
“…It could not yield any data on fasciae and pelvic floor muscles. MRI especially dynamic MRI is one of the most important methods that has been considered in the recent years as it is not invasive and could yield visualization of all soft tissues and pelvic compartments (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Different MRI sequences and protocols could assess these structures.…”
Section: Introductionmentioning
confidence: 99%
“…Is rehabilitation effective in a damaged muscle? Several authors found decreased pelvic floor muscle contraction after delivery in women with LAM avulsion when studying these parameters with vaginal manometry [30] and clinically using either the modified Oxford scale [31] or digital palpation [18]. The novelty of our work is that it offers a functional study of LAM avulsion using AM.…”
Section: Discussionmentioning
confidence: 89%
“…Complete LAM avulsion is currently associated with an increased risk of prolapse and recurrence [15], but no statistically significant association with UI [16] or FI has been found [17]. Because the role of the PRM in the physiology of fecal continence is well known, this lack of association may be due to studies where the role of the sphincter complex was not objectively quantified [18].…”
Section: Introductionmentioning
confidence: 99%
“…During vaginal childbirth, the baby's head distends and stretches the pelvic floor muscles, connective tissue, and nerves, which may then become compromised. The use of forceps, anal sphincter rupture, and episiotomy were found to be the risk factors associated with vaginal delivery [9]. Lenis et al [10] reported that vaginal distention upregulated urethral expression of CCL7 and CD195 immediately after tissue injury in postpartum rats.…”
Section: Structuralmentioning
confidence: 99%